Removal of fenamiphos, imidacloprid, and oxamyl pesticides from water by microalgal Nannochloropsis oculata biomass and their determination by validated HPLC method. Issue 4 (3rd April 2023) - Reyad, Azza G. A.; Abbassy, Moustafa A.; Marei, Gehan I. Kh.; Rabea, Entsar I.; Badawy, Mohamed E. I.
Abstract: The present study assessed the removal of fenamiphos, imidacloprid, and oxamyl pesticides from water using algal Nannochloropsis oculata biomass. Several factors, such as algal biomass concentration, incubation time, and pesticide concentration, were studied for their impact on pesticide removal. Analysis and quantification of pesticides by rapid HPLC have been developed and validated. The optimum conditions were obtained at 15 min, 50 mg/L of pesticide concentration, and 4, 500 mg/L of the algal biomass with 92.24% and 90.43% removal for fenamiphos and imidacloprid, respectively. While optimum parameters of 10 min incubation, 250 mg/L of pesticide concentration, and 2, 750 mg/L of the algal biomass exhibited 67.34% removal for oxamyl. N. oculata, marine microalgae, successively removed different concentrations of the tested pesticides from water, and the algal biomass showed a potential reduction of pesticides in polluted water samples.